(untitled) (Contemporary Education and Teaching Research, 2026)
With the continuous emergence of the “Loving the Good Self” self-care philosophy and the growing public demand for health and well-being, emotional healing and New Chinese wellness practices have gradually become important approaches to addressing the psychological stress and internal emotional consumption experienced by modern individuals, while promoting the coordinated development of both physical and mental health. As a major carrier of China’s outstanding traditional culture, the literature of the Tongcheng School embodies the core principle of self-cultivation and moral nourishment through literary expression. Its elegant classical prose, refined aesthetic temperament, and gentle literati spirit contain profound health-related values, demonstrating strong compatibility with the contemporary “Loving the Good Self” trend, emotional healing practices, and modern New Chinese wellness concepts. This study employs literature review and case analysis to systematically explore the health-related resources embedded in Tongcheng School literature and to examine the feasibility and necessity of integrating these resources into contemporary wellness practices. Based on this analysis, the paper proposes a four-dimensional immersive wellness service model consisting of cultural core, experiential scenarios, technological support, and safe operation, and further clarifies its implementation pathways. Drawing on representative cases, the study also analyzes key challenges in current wellness service development—such as insufficient exploration of cultural connotations and limited alignment between cultural resources and experiential scenarios—and provides corresponding countermeasures and recommendations. The research aims to offer theoretical insights and practical guidance for the dynamic inheritance of Tongcheng School literary heritage and the high-quality development of the New Chinese wellness industry.